2007
DOI: 10.1111/j.1540-6520.2007.00169.x
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Use of Corporate Venturing

Abstract: Corporate venturing (CV) is said to be most productive as a path to superior corporate performance when practiced in a strategic manner. Unfortunately, considerable ambiguity exists concerning what it means in an organizational practice sense to strategically pursue CV. The result is a failure of many companies to fully leverage CV for strategic purposes. Based on a review of the CV literature and findings from a field study of 15 Swedish, U.K., and U.S. corporations, this article describes several models that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
158
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(170 citation statements)
references
References 56 publications
(64 reference statements)
7
158
0
5
Order By: Relevance
“…For the purposes of this paper it is argued that using a firm behavior perspective to understand entrepreneurship is meaningful and the advantages of studying small businesses from this perspective are: (1) firm behavior, as strategy, structure, and performance, is more clearly understood than when only studying the individual entrepreneur; (2) firm behavior is more easily measured that at the individual level; and (3) firm behavior is more manageable (Covin, Miles 2007).…”
Section: Corporate Entrepreneurshipmentioning
confidence: 99%
See 1 more Smart Citation
“…For the purposes of this paper it is argued that using a firm behavior perspective to understand entrepreneurship is meaningful and the advantages of studying small businesses from this perspective are: (1) firm behavior, as strategy, structure, and performance, is more clearly understood than when only studying the individual entrepreneur; (2) firm behavior is more easily measured that at the individual level; and (3) firm behavior is more manageable (Covin, Miles 2007).…”
Section: Corporate Entrepreneurshipmentioning
confidence: 99%
“…A longstanding literature has conceptualized corporate entrepreneurship (CE) as a multidimensional phenomenon which incorporates the behavior and interactions of the individual, organizational, and environmental elements within organizations (Covin, Miles 2007;Dess et al 1999;Kuratko et al 1993;Morris et al 1994;Morris, Kuratko 2002;Zahra 1993). CE refers to an organization's commitments to pursuing new opportunities, creating new units or businesses, innovativeness in terms of products, services and processes, strategic self renewal, constructive risk-taking and pro-activeness (Antoncic, Hisrich 2004;.…”
Section: Corporate Entrepreneurshipmentioning
confidence: 99%
“…Ireland et al (2009) argue that firms that exhibit the strategic intent of continuously and deliberately leveraging entrepreneurial opportunities for growth and advantage-seeking purposes are pursuing a corporate entrepreneurship strategy (CES), and that CV may be part of the strategic vision, entrepreneurial architecture, processes and behaviour that firms utilize. While CV may have an important role in supporting a firm's CES, however, Covin and Miles (2007) do not explicitly argue that a firm's business strategy has to be entrepreneurial in order to pursue strategic CV. Indeed, Tidd and Taurins (1999) indicate that there may be a range of motives for CV: these include market-based motives; growth and diversification; combating cyclical demands of mainstream activities; and organizational learning.…”
Section: Strategic Corporate Venturing In Contextmentioning
confidence: 99%
“…Covin and Miles (2007) have indicated that organizations may take different approaches to the utilization of CV in relation to business strategy, and that CV may either be utilized as part of a business strategy (strategic CV) or not (nonstrategic CV). In addition, they argue that those firms that engage in CV for strategic reasons do so because they realize that innovation is the only way to meet their long-term goals.…”
Section: Strategic Corporate Venturing In Contextmentioning
confidence: 99%
See 1 more Smart Citation